Edición de un libro sobre el proceso artístico para la producción de bodegones fotográficos - Morales Tacuri, Andrea Alfonsina (2013)
The book: “EDICIÓN DE UN LIBRO SOBRE EL PROCESO ARTÍSTICO PARA LA PRODUCCIÓN DE BODEGONES FOTOGRÁFICOS” is an artistic still life manual; it explores those elements of the photographic still lifes that are necessary to convey an idea. Taking as its starting point some concepts traditionally associated with language and communication, sender, message, audience, narrative, signs, the reader will find in these pages the keys to effective visual communication and get a good picture of still life: from issues general as the theme or style, to techniques and specific resources such as composition, light, color, idea. Whether a single object or set of objects, photographic language uses the context and storytelling to build and develop their speech, capturing the attention of the public and allow somehow relate to the history and intent.